The "ICT Competence" from the perspective of Peruvian secondary teachers: more than digital skills (Revista Peruana de Investigación Educativa, 2021)
This communication explores the perceptions of Peruvian teachers about the media, technology and their role in education. Likewise, it analyzes his opinions about the recently created “ICT Competition” in the Peruvian National Curriculum. Based on a qualitative methodology, we conducted five focus groups between May and October 2019 with teachers in the exercise of schools in the city of Lima, Peru. A preliminary conclusion is that, despite its obvious need, medical literacy is not part of the compulsory curricular structure and the “ICT Competence” posed by the new Curriculum is understood more as an instrumental skill than with a sociocultural approach. Teachers show interest in training in media from a critical perspective, although they require important guidance that should be translated into training and awareness programs that allow them to understand the media from a perspective less focused on the artifact and more on information and expression processes promoted by the media.
Keywords: Media education; Teacher education; Teacher qualifications; Informational literacy; Information and communication